Otonomi Daerah Dan Komunikasi Politik Perempuan: (Analisis Gramcian Kandidat Perempuan Parlemen Provinsi DKI Jakarta Tahun 2009) - Umaimah Wahid (Universitas Padjadjaran, 2014)
The research about the women parliament candidacy based on problems, theory, methodology and researchanalysis being utilized by the researcher aims at 1) unveiling affirmative action policy in accordance to the2003 Public Election regulation (UU) and the 2008 political party regulation that are suitable policy along withefforts to enhance women representativeness in parliament within regional autonomy framework; 2) elaboratingpolitical party supports towards quota fulfillment process of 30 percent in line with the 2009 public electionregulation; 3) describing and criticizing mass media roles in the process of the political communication of womencandidates of DKI Jakarta Province in 2009; 4) discovering and exploring quality of the political communicationof women candidates of DKI Jakarta Province 2009; 5) highlighting women efforts and struggles regarding theregulation of political quota and regional autonomy are so-called ‘counter hegemony’ movement. Paradigmused in the research is critical paradigm with Gramcsian analysis model. Theory and concept of this research areAntonio Gramcsi’s thoughts; hegemony-counter hegemony, political network alliance, political communication,radical feminism, mass media in the New Marxist perspective (Gramcsian) and regional autonomy concept.The research uses qualitative approach with case study method and feminist research as well as equipped bymethod of the Gramcsian-Marxist analysis. Results and discussion of the research argue that women have beenundergoing marginalization both culturally and structurally in the political realm resulting in injustice of theirrepresentativeness in parliament. The notion becomes rooted in the social structure and system and has been goingas a cultural system which is patriarchy system. The women altogether have to establish and belong to a solidnetwork alliance to give pressure towards the government; those are in power and the state in order to transformconditions of women representativeness in parliament. They are therefore expected to have bargaining positionthat is balanced or even stronger with the state. The position is needed by women in that they can compete withmen and create broader opportunity by which they achieve it by the release of the 2009 political party regulationand the running of the regional autonomy regulation. In the Gramcsi’s concept, the equality of bargaining positionbetween women movement, represented as civil society and the state represented as political community highlylikely produce conceptual/intellectual and practical clashes to establish new hegemony whose consequence isto prosper woman community and broader civil society as well as political community. In this phase, Gramcsinames it as ‘counter hegemony’ movement in which women can present themselves and bear new hegemony afterwinning the conceptual war against the old hegemony. The women’s struggles to run candidacy of The 2009 DKIregional election took a form of ‘counter hegemony’. The effort was undertaken so that the women can owe highbargaining position in politics that is influenced by the other power namely mass media. The need to supports ofmedia industry is inevitable. Media industry, as institution having capital ideology, might highly possible be usedby women movement/ the civil. In addition, women can take benefits from media to assist struggles of ‘counterhegemony’. As a consequence, the women’s struggles of counter hegemony are complicated to do due to partialand incomprehensive efforts. The women political candidates of DKI Jakarta possess resistant movement spirit orfighting movement to transform cultural values of patriarchy especially in politics. In this notion, it is evident thatemancipation ideology is not effective to strengthen the movement unless it is as communal vision and missionfrom elements of struggles that can produce women great energy to achieve their goals. The energy is no other than‘collective will’ considered as fighting ideology which is necessary therein fighting ideas of women have constantand significant energy.Keywords : regional autonomy, political communication, Gramcsian Analysis, women parliament candidacydkijakarta 2009)